Saving Stuyvesant Town : How One Community Defeated the Worst Real Estate Deal in History - Garodnick, Daniel R., 1972- (Book collections on Project MUSE., 2021)
"The story of the 2006 to 2015 efforts by residents of Stuyvesant Town and Peter Cooper Village on Manhattan's East Side, and New York City Council Member Dan Garodnick, as they fought to preserve the United States' largest rental community as middle class housing"--